An integrated decision support system for improving wildfire suppression management - Lourenço, Miguel (2021)
Funding Information: This work was financially supported by FCT (National Foundation of Science and Technology) within the Research Unit CTS?Centre of Technology and Systems, UIDB/00066/2020, and the Project forester (PCIF/SSI/0102/2017). We would like to thank the authorities from the municipality of Ma??o, in particular to Engineer Ant?nio Louro, for the valuable support in establishing the user requirements and the feedback for the system?s validation. Special thanks to the Adjunct of National Operations in the National Command of Security Operations (CNOS) part of the National Authority of Civil Protection (ANPC) Alexandre Penha, for their input in the early stages of this work.